Integrating Information Technology and Transformational Leadership for Improved Employee Performance in Public Service - Putranto, Andy Joko; Kistyanto, Anang; Wardoyo, Dewie Tri Wijayati (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Several factors influence the performance of Service Employees, both external and internal. Therefore, this research aims to find out how the use of Information Technology affects the performance of Service Employees, to find out how the transformational leadership style affects the Performance of Service Employees, to find out how the Use of Information Technology and transformational leadership style affects the performance of employees at the Magetan Population and Civil Registration Service. This quantitative research was conducted at the Magetan Population and Civil Registry Service in 2024. Data was collected through documents and questionnaires, with validity and reliability tests on 81 respondents. Research data was analyzed using multiple regression techniques. The research results show that the use of information technology influences the performance of service employees, and the transformational leadership style influences the performance of service employees. Information technology and transformational leadership style significantly affect KKN learning achievement at the Magetan Population and Civil Registry Service. Based on the results of this research, it is recommended that department heads improve employee performance by implementing a transformational leadership style and learning to utilize information technology to develop employee performance.